Correction: Genetic and morphological divergence in the warm-water planktonic foraminifera genus Globigerinoides. - Raphaël Morard; Angelina Füllberg; Geert-Jan A Brummer; Mattia Greco; Lukas Jonkers; André Wizemann; Agnes K M Weiner; Kate Darling; Michael Siccha; Ronan Ledevin; Hiroshi Kitazato; Thibault de Garidel-Thoron; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0225246.].